Accuracy of pulse oximetry in detection of oxygen saturation in patients admitted to the intensive care unit of heart surgery: comparison of finger, toe, forehead and earlobe probes - Sohila Seifi; Alireza Khatony; Gholamreza Moradi; Alireza Abdi; Farid Najafi (BMC, 2018)
Abstract Background Heart surgery patients are more at risk of poor peripheral perfusion, and peripheral capillary oxygen saturation (SpO2) measurement is regular care for continuous analysis of blood oxygen saturation in these patients. With regard to controversial studies on accuracy of the current pulse oximetry probes and lack of data related to patients undergoing heart surgery, the present study was conducted to determine accuracy of pulse oximetry probes of finger, toe, forehead and earlobe in detection of oxygen saturation in patients admitted to intensive care units for coronary artery bypass surgery. Methods In this clinical trial, 67 patients were recruited based on convenience sampling method among those admitted to intensive care units for coronary artery bypass surgery. The SpO2 value was measured using finger, toe, forehead and earlobe probes and then compared with the standard value of arterial oxygen saturation (SaO2). Data were entered into STATA-11 software and analyzed using descriptive, inferential and Bland-Altman statistical analyses. Results Highest and lowest correlational mean values of SpO2 and SaO2 were related to finger and earlobe probes, respectively. The highest and lowest agreement of SpO2 and SaO2 were related to forehead and earlobe probes. Conclusion The SpO2 of earlobe probes due to lesser mean difference, more limited confidence level and higher agreement ration with SaO2 resulted by arterial blood gas (ABG) analysis had higher accuracy. Thus, it is suggested to use earlobe probes in patients admitted to the intensive care unit for coronary artery bypass surgery. Trial registration Registration of this trial protocol has been approved in Iranian Registry of Clinical Trials at 2018-03-19 with reference IRCT20100913004736N22. "Retrospectively registered."